2017
DOI: 10.2147/ndt.s122615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the risk factors of depressive disorders comorbid with obstructive sleep apnea

Abstract: ObjectiveOverlap of obstructive sleep apnea (OSA) complicates diagnosis of depressive disorder and renders antidepressant treatment challenging. Previous studies have reported that the incidence of OSA is higher in patients with depression than in the general population. The purpose of this article was to investigate clinical risk factors to predict OSA in depression disorders.MethodsA total of 115 patients diagnosed with major depressive disorder (MDD) and bipolar disorder (in a major depressive episode), who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…On the other hand, cognitive impairment may be a consequence of EDS due to sleep fragmentation (Zhou et al, 2016). In the context of mood disorders with OSA, a higher degree of depressive and anxiety symptoms is frequently described (Acker et al, 2017;Cai, Xu, Wei, Sun, & Chen, 2017;Ejaz, Khawaja, Bhatia, & Hurwitz, 2011;Schroder & ÓHara, 2005). Depression in particular is closely linked with OSA due to common clinical symptoms (Acker et al, 2017;BaHammam et al, 2016;Ejaz et al, 2011;Fidan, Unlu, Sezer, Gecici, & Kara, 2007;Naqvi et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, cognitive impairment may be a consequence of EDS due to sleep fragmentation (Zhou et al, 2016). In the context of mood disorders with OSA, a higher degree of depressive and anxiety symptoms is frequently described (Acker et al, 2017;Cai, Xu, Wei, Sun, & Chen, 2017;Ejaz, Khawaja, Bhatia, & Hurwitz, 2011;Schroder & ÓHara, 2005). Depression in particular is closely linked with OSA due to common clinical symptoms (Acker et al, 2017;BaHammam et al, 2016;Ejaz et al, 2011;Fidan, Unlu, Sezer, Gecici, & Kara, 2007;Naqvi et al, 2014).…”
mentioning
confidence: 99%
“…When the effect of CPAP is detected, improvement depends on the duration of CPAP use, both in the context of an average number of hours per night and the number of months since the start of CPAP treatment (Antic et al, 2011;Ferini-Strambi et al, 2003;Sforza & Roche, 2012). Most studies on the subject have reported a significant association between CPAP treatment and decreased depressive and anxiety symptoms (Cai et al, 2017;Celik et al, 2016). Longitudinally, CPAP treatment improves mood disorders and vigilance, which is associated with a lower frequency of traffic accidents (Jackson et al, 2011;Yamamoto, Akashiba, Kosaka, Ito, & Horie, 2000).…”
mentioning
confidence: 99%
“…The first these argued that OSAS patients experienced a high level of depression, while the latter claimed that the depression comorbidity was coincidental and not significant. The third stated that OSAS was not associated with depression [32]. There are even studies which reported that there was a negative correlation between total depression scores and OSAS [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Patients who do not improve after taking antidepressant therapy and have symptoms of OSA should be screened for OSA and be treated with CPAP if OSA is diagnosed. [19][20][21] Patients who were diagnosed with MDD and treated by antidepressants but saw no improvement started to see their depression symptoms resolved when they began taking CPAP therapy. 12 Mood disorder and depressive symptoms associated with OSA can be improved by CPAP therapy, but the effect of treatment can take longer depending on the variations and severity of the mood symptoms.…”
Section: Depression and Obstructive Sleep Apneamentioning
confidence: 99%